Evolution Law of Floor Fracture Zone above a Confined Aquifer Using Backfill Replacement Mining Technology - Shan Ning; Weibing Zhu; Xiaoyong Yi; Laolao Wang (Geofluids)
Disturbances owing to coal mining result in the movement and failure of floor strata. Mining-induced fractures within the floor may propagate to the confined aquifer, thereby causing water inrush disasters. In this study, we propose using strip mining and backfill replacement mining above the confined aquifer to investigate the failure depth of the floor. The problem is simplified as a distributed force model on a half-plane body. First, the stress disturbance of the floor during strip mining is calculated and the results are combined with the von Mises yield criterion. Then, the destruction of the floor after replacing the remaining coal pillars is explored. The results show that the widths of the strip mining face and coal pillars play an important role in affecting the failure depth of the floor: the greater the width, the larger the failure depth. Based on the parametric study results, the mining face and retention coal pillar width of 20 m is sufficient to prevent the occurrence of water inrush accidents. After the replacement of the remaining coal pillars, the failure area of the floor rock mass increases, but the maximum failure depth remains unchanged. Finally, we employed field measurement techniques at the Bucun coal mine to monitor the shear and vertical strains of the floor. The data collected was compared with the predicted results obtained from the proposed theoretical model. Good agreement was found between the monitoring and calculation results, which demonstrate the effectiveness of the proposed method.